Projeto de Lei n° 2.302/2019, violência estrutural e violência criminal na cidade de São Luís do Maranhão - ROCHA, Mauro Costa da (2024)
The research focuses on investigating to what extent unemployment, one of the spectrums that make up structural violence, the result of a process of automation in the production model experienced more intensely nowadays, can be considered as an element that influences, automatically and strongly, the direction of this mass of idle people towards the world of criminal violence. To this end, it was discussed, initially, about the great revolutions experienced in the civilized world in the course of its history, making brief but important considerations about how the State has behaved throughout history in the economic scenario, making a digression of each of the periods that presented themselves to us, until we reach the current disruptive moment called the Fourth Industrial Revolution; It was also analyzed, in a more detailed way, the benefits resulting from automation for society, as well as whether it can be considered as a factor of aggravation of the denial of the existential minimum, that is, of the establishment of a framework of structural violence, notably structural unemployment, through the analysis of empirical data; It was also discussed about the possible relationship between capital, labor and formal social control within the neoliberal model. , analyzing the economic models already used in social evolution, establishing a link between the way in which the latter is used by the neoliberal model to achieve the objectives of the social elites; Finally, constituting the core of the work, the Bill 2,302/2019 was analyzed, as an example, whose purpose is to allow the operation of self-service pumps operated by the consumer himself at gas stations moving on to a detailed study about the neoliberal economic model replicated in Brazil and its effects in the context of criminal violence and, finally, reaching the neuralgic point of the research, that is, whether automation can be considered as a triggering element of both structural and criminal violence. The socio-legal-critical scientific method was chosen because it is effective in the analysis of the legal phenomenon, along with inductive reasoning. As a method of procedure, the legal-diagnosis was observed, in order to establish a link between unemployment, structural violence and criminal violence based on the data collected and, with a detailed bibliographic survey, to analyze the aspects related to the crime numbers that supposedly flow from the relationship between those elements in the social body. Quantitative research techniques were used, as well as content analysis to support the theoretical basis, in addition to extensive research of documents issued by public and private entities that carry out research and diagnoses in the country related to social indicators, such as the number of people living below the poverty line, unemployment/loss of jobs and criminal violence and/or crime.